Influence of air and sea baroclinic effects on the structure of the boundary layers - Ly, Le Ngoc (Vietnam Journal of Mechanics, 1981)
The influence of Air and Sea baroclinic effects on the boundary structure is studied by various numerical experiments for different baroclinic parametres Γxi, Γyi. The resulte obtained in calculation show that the baroclinic effects have strong influence on the structure of both boundary layers, especially on the profiles or Air and Sea turbulence coefficients.